The Risk of Implementing Green Retrofitting in High-Rise Buildings Based on Work Breakdown Structures to Improve Quality of Resource Planning and Cost Accuracy - Bernadette Detty Kussumardianadewi; Yusuf Latief; Ayomi Dita Rarasati; Muhammad Arkan Akhyari; Muhammad Faizurrahman (Engineering Proceedings)
The building sector accounts for more than one-third of final energy consumption worldwide. Green retrofitting, which is part of the green building activities, is one of the main factors in achieving the target of zero carbon emissions by 2060. Green retrofitting is a viable way to reduce greenhouse gas (GHG) emissions and energy consumption. The risks in green retrofitting work activities have not been studied much, even though the risks in green retrofitting projects are likely to be greater and more complex than the risks in conventional projects. This is reflected in the small application of customization in developing countries, one of which is Indonesia. Through the calculation of the risk matrix between probability and impact, a high risk was obtained from the relationship between risk and correlated resources, and it had a positive impact on the work breakdown structure (WBS). The results obtained show that complexity factors consisting of labor, materials, equipment, work activities, work methods, and scope/work package affect the success of the project, then the risk handling strategy that needs to be implemented is to set the right priorities. A focused project team allocates resources wisely. Knowing the probability of events and impacts arising from the non-implementation of the WBS, we identified sources of risk factors and high risk in the implementation of green retrofitting work based on the WBS based on the Greenship Existing Building Rating Tools and PUPR RI Regulation Number 21 of 2021 applicable in Indonesia, its effect on resource planning, and cost accuracy.